IMPACT OF PATIENT SATISFACTION IN THERAPEUTIC COMMUNICATION ASPECTS AFTER IMPLEMENTATION OF CLINIC SUPERVISION BY NURSE MANAGER - Grace Aneke Merentek; Asnet Leo Bunga; Wilhemus Hary Susilo (Jurnal Ilmiah Perawat Manado (Juiperdo), 2019)
Background: Nursing is an activity of providing care to individuals, families, groups or communities both sick and healthy as a form of professional service where the nursing practice is a service organized by nurses in the form of nursing care. One of the tasks of the nursing manager is to coordinate through supervision/supervision. Aims: This study aims to analyze, explore the effect of training and implementation of clinical supervision on nurse-patient therapeutic communication. Methods: This study used quasi-experimental design research before and after post control group. The number of samples in this study was 100 respondent nurses and patients who were divided into 75 intervention groups who were given training and implementation of supervision and control groups of 25 respondents. Results: The study showed that the improvement in the supervision capability of the headroom clinics increased significantly (p = 0,000) after training and implementation of clinical supervision. Patient satisfaction with therapeutic communication has increased with a value (p = 0,000). Conclusion: Implementation of clinical supervision contributed to patient satisfaction and therapeutic communication of patient nurses by 17.6%, while 82.4% was influenced by other variables (quality of service, hospital products). This study further recommends the implementation of clinical supervision to be one of the models in developing the quality of nursing services.